EMPOWERING INDONESIAN MUSLIM MIGRANT WOMEN THROUGH ENTREPRENEURSHIP TRAINING: A COMMUNITY ENGAGEMENT PROGRAM IN KUALA LUMPUR - Jatiningrum, Citrawati; Abadi, Satria; Fauzi, Fauzi; Gumanti, Miswan; Sudewi, Sudewi; Maseleno, Andino (PENA DIMAS: Jurnal Pengabdian Masyarakat, 2025)
Women's empowerment in entrepreneurship plays a vital role because it equips individuals to succeed, fostering innovation, economic growth, and societal impact. These community service international programs have been recognized as a potential means to promote women's empowerment for household migrants and entrepreneurship by providing them with opportunities to develop skills, access resources, and engage in entrepreneurial training. This community service uses the Asset-Based Community Development method, which strengths-focused, participatory framework that empowers community teams to carry out the activity from two higher education institutions, Indonesia-Malaysia University. There are Institut Bakti Nusantara (IBN) Lampung Indonesia and Universiti Pendidikan Sultan Idris Malaysia, which are some of the care activities driving the empowerment of women migrants in Kuala Lumpur. The result of international community service was that it successfully carried out positive responses from participants, which can be seen from the outcomes of training the participants from the household migrant Muslims in Kuala Lumpur. Entrepreneurship training participants indicated a majority increase in knowledge and skills in entrepreneurship. Therefore, women's empowerment in entrepreneurship training is not just about individual success—it transforms communities by fostering resilience, innovation, and economic progress.